Two Squares in a Barrel: An Axially Disubstituted Conformationally Rigid Aliphatic Binding Motif for Cucurbit[6]uril - Jelínková, Kristýna; Závodná, Aneta; Kaleta, Jiří; Janovský, Petr; Zatloukal, Filip; Nečas, Marek; Prucková, Zdeňka; Dastychová, Lenka; Rouchal, Michal; Vícha, Robert (The Journal of organic chemistry, 2023)
Novel binding motifs suitable for the construction of multitopic guest-based molecular devices (e.g., switches, sensors, data storage, and catalysts) are needed in supramolecular chemistry. No rigid, aliphatic binding motif that allows for axial disubstitution has been described for cucurbit[6]uril (CB6) so far. We prepared three model guests combining spiro[3.3]heptane and bicyclo[1.1.1]pentane centerpieces with imidazolium and ammonium termini. We described their binding properties toward CB6/7 and α-/β-CD using NMR, titration calorimetry, mass spectrometry, and single-crystal X-ray diffraction. We found that a bisimidazolio spiro[3.3]heptane guest forms inclusion complexes with CB6, CB7, and β-CD with respective association constants of 4.0 × 104, 1.2 × 1012, and 1.4 × 102. Due to less hindering terminal groups, the diammonio analogue forms more stable complexes with CB6 (K = 1.4 × 106) and CB7 (K = 3.8 × 1012). The bisimidazolio bicyclo[1.1.1]pentane guest forms a highly stable complex only with CB7 with a K value of 1.1 × 1011. The high selectivity of the new binding motifs implies promising potential in the construction of multitopic supramolecular components.